Fundamentals of signals and systems a building block approach - Cha, Philip D. (Cambridge University Press, 2006)
Key concepts such as the orthogonality principle and the Fourier transformation begin this textbook, which goes on to discuss modelling, analysis and design of electrical and mechanical systems using real-world examples.